Pediatric Multiple Sclerosis—A Challenging Demyelinating Disease: Case Report and Brief Review of the Literature - Regina Célia Ajeje Pires de Albuquerque; Raquel Siqueira Leonel de Paula; Manuelina Mariana Capellari Macruz Brito; José Roberto Lopes Ferraz Filho; Lucas Crociati Meguins (Case Reports in Pediatrics)
Multiple sclerosis (MS) is an inflammatory, demyelinating, neurodegenerative disorder of the central nervous system (CNS) of unknown etiology. The peak onset is between age 20 and 40 years and usually affects more women than men. Although much knowledge has been achieved on the diagnosis and treatment of adult patients with MS, it remains a matter of debate and controversy in childhood. We present a case of MS in 9-year-old girl, review the current state of the knowledge on pediatric MS, and discuss the available tools for the diagnosis and treatment.